Load Balance Strategies for Devs Approximated Parallel and Distributed Discrete-Event Simulations - Marin-Caihuan, J; Inostrosa-Psijas, A (Institute of Electrical and Electronics Engineers Inc., 2015)
DEVS is a formalism for modeling and analysis of discrete event systems. PDEVS is an extension of DEVS for supporting Parallel and Discrete Event Simulation (PDES). PCD++ is a simulation platform that supports parallel simulations of DEVS models, where the model component allocation in processors is not an automatic process. This can be a time consuming task requiring knowledge of communication patterns among model components. In this paper, we propose and evaluate different allocation strategies devised to improve load balance of parallel DEVS simulations. The experimentation is made on a Web search engine application whose workload is featured by dynamic and unpredictable user query bursts, and high message traffic among processors. © 2015 IEEE.